Undifferentiated Carcinoma with Osteoclast-like Giant Cells of the Pancreas: Molecular Genetic Analysis of 13 Cases - Hrudka, Jan; Kalinová, Markéta; Ciprová, Vanda; Moravcová, Jana; Dvořák, Radim; Matěj, Radoslav (International journal of molecular sciences, 2024)
Undifferentiated carcinoma with osteoclast-like giant cells (UCOGC) of the pancreas is a rare malignancy regarded as a subvariant of pancreatic ductal carcinoma (PDAC) characterized by variable prognosis. UCOGC shows a strikingly similar spectrum of oncogenic DNA mutations to PDAC. In the current work, we analyzed the landscape of somatic mutations in a set of 13 UCOGC cases via next-generation sequencing (NGS). We detected a spectrum of pathogenic or likely pathogenic mutations similar to those observed in PDAC following previously published results (10 KRAS, 9 TP53, 4 CDKN2A, and 1 SMAD4, CIC, GNAS, APC, ATM, NF1, FBXW7, ATR, and FGFR3). Our results support the theory that UCOGC is a variant of PDAC, despite its unique morphology; however, a UCOGC-specific genomic signature as well as predictive markers remain mainly unknown. Programmed death ligand 1 (PD-L1) status remains an important predictive marker based on previous studies.
Keywords: osteoklasty; obrovské buňky; mutace; Pancreatic Neoplasms; Osteoclasts; Humans; Giant Cells; lidé; Pancreas; Molecular Biology; nádory slinivky břišní; pankreas; Mutation; duktální karcinom slinivky břišní; Carcinoma, Pancreatic Ductal; molekulární biologie